Relasi Gender Feminin dan Cinderlla Complex dengan Motivasi mempertahankan Keutuhan Keluarga: Studi Kasus Korban KDRT di PPT Jawa Timur - Nina Nuriyah Maarif (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
Abstract: This article reports on research conducted with 30 of those housewives who were victims of domestic violence who reported to the East Java Service Centers (Pusat Pelayanan Terpadu/ PPT). It attempts to examine the correlation between the role of feminine gender and Cinderella complex to the motivation of women victims of domestic violence in maintaining the integrity of the household. This study utilized quantitative correlational methods. Using Kendall Tau statistical analysis, which was processed with SPSS 11.5 and 14.00 for Windows, this research found that the roles of feminine gender and cinderella complex had a relationship with the motivation of victims of domestic violence in maintaining household integrity with a significance level of 0.007 where P <0.05 (Cinderella complex) and 0.023 where P <0.05 (feminine gender role).